2020
DOI: 10.1002/jso.25814
|View full text |Cite
|
Sign up to set email alerts
|

Refining the indications for neoadjuvant chemotherapy for patients with HER2+ breast cancer: A single institution experience

Abstract: Background: We aim to compare the clinical outcomes of patients with early-stage HER2+ breast cancer treated with adjuvant chemotherapy (AC) and neoadjuvant chemotherapy (NAC).Methods: Patients with non-metastatic HER2+ breast cancer treated from 2009 to 2018 at our institution comprised our study cohort (n = 1254). Pathologic complete response (pCR) was defined as the absence of invasive disease in the breast and axilla after NAC. Log-rank, Kaplan-Meier, and inverse probability of treatment weighting were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…FOXO3a is a member of the FOXO family; it enters the nucleus after binding with β-catenin, where it was reported to accelerate the self-renewal of cancer cells, thus promoting the formation of tumors ( 37 , 38 ). FOXO3a has also been discovered to combine with the transcription regulatory machinery of different target genes in the nucleus to serve a role in transcriptional regulation, in addition to participating in the proliferation, migration, invasion and apoptosis of cells ( 12 , 39 ). FOXO3a was also discovered to serve a role in abnormal activity, stress tolerance and the metabolic homeostasis of tumor cells by regulating the expression of cell cycle-related factors and apoptosis-related factors effect ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…FOXO3a is a member of the FOXO family; it enters the nucleus after binding with β-catenin, where it was reported to accelerate the self-renewal of cancer cells, thus promoting the formation of tumors ( 37 , 38 ). FOXO3a has also been discovered to combine with the transcription regulatory machinery of different target genes in the nucleus to serve a role in transcriptional regulation, in addition to participating in the proliferation, migration, invasion and apoptosis of cells ( 12 , 39 ). FOXO3a was also discovered to serve a role in abnormal activity, stress tolerance and the metabolic homeostasis of tumor cells by regulating the expression of cell cycle-related factors and apoptosis-related factors effect ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…For HER2+ breast cancer patients in neoadjuvant setting, the standard regimen to date was chemotherapy and trastuzumab (AC-TH, AC-PH, or TCbH), in which the pCR rates of 50% or more can be achieved (15,(19)(20)(21). TCbH has often been preferred by clinicians due to its lower cardiotoxicity profile, in which weekly regimens are much more effective than the threeweek schedule (69% vs. 41%; p = 0.03) (15,21).…”
Section: Discussionmentioning
confidence: 99%
“…This is, to our knowledge, one of the first studies to report an impact of treatment strategy (NAC vs. AC) in a subset of patients: the HER2-positive population. In a recent study of Pomponio et al, using IPTW to deal with the selection bias showed no difference between AC and NAC strategy in early HER2-postive BC [30]. Many studies have reported higher rates of breast-conserving surgery in patients treated with NAC, but a recent EBCTCG meta-analysis [13] found that NAC was as effective as AC in reducing the risk of distant recurrence and death from BC.…”
Section: Discussionmentioning
confidence: 99%